(untitled) (SCIENCE TIME JOURNAL, 2026)
The advent of computational linguistics has fundamentally transformed the analysis of text complexity and the preservation of cultural heritage within the Indo-European language family. This article explores how computational methodologies, including natural language processing (NLP), machine learning, and phylogenetic analysis, enhance our understanding of phonetic, morphological, syntactic, and semantic complexities across diverse Indo-European languages. By leveraging digital corpora, treebanks, and automated annotation tools, researchers can uncover historical linguistic relationships, democratize access to underrepresented languages, and support revitalization efforts. Furthermore, the digitization and contextualization of ancient texts facilitate cross-cultural scholarship and safeguard endangered linguistic traditions.